Detrital zircon population of the Middle Triassic sediments in the eastern Sichuan Basin, South China and implications for tectonic setting - Liu, Tianjia; Zhang, Dianwei; Zhai, Yonghe; Liu, Xiangbai; Zhang, Lei; Fan, Lingxiao; Cheng, Chuanjie; Fang, Shaobo (Frontiers in Earth Science, 2025)
The closure of the Paleo-Tethys Ocean lead to the collisional amalgamation of the various blocks including South China, Indochina and North China blocks, which results in the formation of the Qinling and Ailaoshan orogenic belts. But the tectonic evolution of the two orogenic belts remains highly debated during the Triassic. The eastern Sichuan Basin, preserving the complete Triassic depositional successions, offers crucial insight into the tectonic evolution of the two orogenic belts in this period. Detailed geological investigations and provenance analyses using detrital zircon U–Pb–Hf isotopic data and trace element compositions are conducted on the Middle Triassic Leikoupo Formation samples in the eastern Sichuan Basin. The age distribution of the middle part of the Leikoupo Formation (Member-2) shows five age clusters of 290∼230 Ma, 330∼290 Ma, 470∼390 Ma, 900∼840 Ma and 1400∼1200 Ma, and those of the top (Member-3) show four age clusters of 250∼238 Ma, 330∼300 Ma, 960∼900 Ma and 2550∼2450 Ma. Considering proximity and widespread distribution, the sediments of the sample at middle part are interpreted to source from the Ailaoshan orogenic belt, the North Qinling orogenic belt and late Paleozoic granites in the Cathaysian Block. The samples at the top primarily originated from the Ailaoshan orogenic belt, basement rocks and Neoproterozoic granites in the Yangtze Block and late Paleozoic granites in the Cathaysian Block. Provenance analysis indicates that the North Qinling orogenic belt can provide a large amount of materials for the Middle Triassic, which suggests this belt was in an uplift stage and was the extension of the Caledonian orogeny since the early Paleozoic. Combining the obtained ages, published data and lithofacies paleogeography, the Early-Middle Triassic source rocks have contributions from the early Mesozoic granites in Ailaoshan orogenic belt, which suggests the Ailaoshan orogenic belt has experienced initial tectonic uplift in the Early Triassic. This initial uplift is related to the collisional amalgamation between the South China Block and Indochina Block.